Implementation Of Problem-Based Management Model On Improving School Quality Culture At Mts Nurul Iman Tanjung Morawa - Yenni Khairani Pane; Nathanael Sitanggang; Joharis Lubis (International Journal of Educational Research & Social Sciences, 2021)
School quality can be seen from the culture that lives and is developed by the school community. School culture is a set of values ​​that underlie behavior, traditions, daily habits, and symbols practiced by principals, teachers, administrative officers, students and the community around the school. School quality is one of the central issues in national education in addition to other issues such as equity, relevance, and efficiency of school management. Currently, efforts to improve the quality of schools continue to be carried out by various parties, both by the school foundation and the government itself. These efforts are based on an awareness of the importance of the role of education in the development of human resources and Nation Character Building for the progress of society and the nation. The dignity of a nation is largely determined by the quality of its education. In fact, many school principals are very concerned about the importance of building a school atmosphere, classroom atmosphere, building harmonious relationships to support the formation of norms, beliefs, attitudes, characters, and achievement motives so that they grow into positive thinking attitudes of school citizens.